Towards a better understanding of the L2 Learning Experience, the Cinderella of the L2 Motivational Self System - Dörnyei, Zoltán (Studies in Second Language Learning and Teaching, 2019)
The theoretical emphasis within the L2 Motivational Self System has typically been on the two future self-guides representing possible (ideal and ought-to) selves, leaving the third main dimension of the construct, the L2 Learning Experience, somewhat undertheorized. Yet, this third component is not secondary in importance, as evidenced by empirical studies that consistently indicate that the L2 Learning Experience is not only a strong predictor of various criterion measures but is often the most powerful predictor of motivated behavior. This paper begins with an analysis of possible reasons for this neglect and then draws on the notion of student engagement in educational psychology to offer a theoretical framework for the concept. It is proposed that the L2 Learning Experience may be defined as the perceived quality of the learners’ engagement with various aspects of the language learning process.